2018 Pyeongchang Winter Olympics as Peace Instrument of South and North Korea - Mulyaman, Darynaufal; Ismail, Achmad; Tambunan, Issuwari; Manurung, Engelita Evelin; Pangasah, Gabriella A. (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
There are various ways for countries to fulfill their national interests, one of which is through diplomacy, especially in the field of sports. That's what happened at the 2018 Pyeongchang Winter Olympics. This sporting event was used as a way to find peace between South Korea and North Korea. This research seeks to explain how sport can act as an instrument to achieve peace. This research also aims to provide a specific picture of how sport can have a positive impact on countries in conflict, in this context South Korea and North Korea. Sports support for development and peace can be achieved because sport provides a catalyst for non-military diplomacy. Therefore, sport is seen and considered as an important social link in bilateral and multilateral relations. This research is qualitative research with a case study method that uses data collection and analysis through literature study. Data was collected and analyzed using a liberalism perspective with a functionalism approach and the concept of sports diplomacy. The result is that the success of the 2018 Pyeongchang Winter Olympics has resulted in increased positive interaction between South Korea and North Korea, especially in sports partnerships.